Analisis Pengaruh Produk Domestik Regional Bruto, Indeks Pembangunan Manusia, Tingkat Partisipasi Angkatan Kerja Dan Rata-Rata Pengeluaran Perkapita Terhadap Upah Minimum Kabupaten/Kota di Karesidenan Pekalongan Tahun 2017-2021 - Rindana Rahmawati Kusumaningrum; Siti Fatimah Nurhayati (STIE AMKOP, 2023)
The purpose of this study was to determine and analyze the effect of gross regional domestic product, human development index, labor force participation rate, and average per capita expenditure on the district/city minimum wage in the Pekalongan residency in 2017-2021. This study uses secondary data in the form of panel data consisting of cross sections of 7 regencies in the Pekalongan Residency and time series for the period 2017-2021 using a statistical software tool, namely Eviews. The approach method used in estimating panel data for this study is the Fixed Effect Model (FEM). The results of the study concluded that gross domestic product has a positive effecton district/city minimum wages, the human development index has no effect on district/city minimum wages, which means that this result rejects the initial hypothesis, while the labor force participation rate has a negative effect on district/city minimum wages. and the average per capita expenditure has a positive effect on the district/city minimum wage in the Pekalongan residency. The results of the F test indicate that the model exists. The R-squared is 0.9522, meaning that 95.22% of the variation in the district/city minimum wage variable can be explained by the GRDP, HDI, TPAK and average per capita expenditure variables. The remaining 4.78% is influenced by variables or other factors not included in the model Keywords: Minimum wage, gross regional domestic product, human development index, labor force participation rate, average per capita expenditure